SEMANTIC TRANSFORMATIONS OF TOPONYMS IN THE PROCESS OF LITERARY TRANSLATION (World Bulletin of Social Sciences, 2025)
Toponyms in Uzbek literature carry deep cultural and historical meanings that often change during translation into English. This study explores how these place-names undergo semantic transformations such as transliteration, adaptation, or omission. It analyzes how meaning is preserved or altered through different translation strategies. The results highlight the importance of maintaining cultural authenticity while ensuring clarity for target readers.